The Influence of Ag(I) Ions on the Kinetics of Oxidation of Safranine by Peroxodisulphate - Agarwal, G.L.; Chourasia, Rajesh (Asian Journal of Chemistry, 2010)
The influence of silver ions on the kinetics of safranine, an azine dye, by peroxodisulphate has been ivestigated in the presence of sulphuric acid colorimetrically. It was found that the rate is independent of the concentration of safranine but first order dependent with respect to the concentration of S2O82- and Ag(I). The reaction exhibits negative salt effect. Acrylonitrile greatly inhibits the rate. A radical mechanism has been proposed to explain the observed results.